2004
DOI: 10.1164/rccm.200404-543oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluticasone on Systemic Markers of Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: Systemic inflammation is present in chronic obstructive pulmonary disease (COPD), which has been linked to cardiovascular morbidity and mortality. We determined the effects of oral and inhaled corticosteroids on serum markers of inflammation in patients with stable COPD. We recruited 41 patients with mild to moderate COPD. After 4 weeks during which inhaled corticosteroids were discontinued, patients were assigned to fluticasone (500 mcg twice a day), oral prednisone (30 mg/day), or placebo over 2 weeks, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
198
5
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(226 citation statements)
references
References 38 publications
9
198
5
14
Order By: Relevance
“…We did not confirm the work of Sin and colleagues, who demonstrated a 50% decrease in serum CRP following only two weeks of the same dose of inhaled fluticasone [Sin et al 2004]. Our subjects had substantially more advanced COPD (FEV 1 of 1.07 L vs. 1.67 L, respectively) and were slightly older (71 years vs. 64 years, respectively) than those in Sin and colleagues' study.…”
Section: Discussioncontrasting
confidence: 96%
“…We did not confirm the work of Sin and colleagues, who demonstrated a 50% decrease in serum CRP following only two weeks of the same dose of inhaled fluticasone [Sin et al 2004]. Our subjects had substantially more advanced COPD (FEV 1 of 1.07 L vs. 1.67 L, respectively) and were slightly older (71 years vs. 64 years, respectively) than those in Sin and colleagues' study.…”
Section: Discussioncontrasting
confidence: 96%
“…As these medications are widely prescribed as anti-inflammatory agents to patients with CF, it was not possible to exclude patients who were receiving this therapy. In adults with chronic obstructive pulmonary disease, inhaled glucocorticoids have been shown to have systemic anti-inflammatory activity [44]. We are not aware of previous serum cytokine measurements in patients with CF following treatment with these agents.…”
Section: Discussionmentioning
confidence: 97%
“…ICS, even in high doses, fail to suppress inflammation in COPD lungs and airways and this may be due to an active resistance mechanism linked to a reduction in histone deacetylase 2 expression [161]. Observational studies suggested that ICS reduces all causes of mortality in COPD patients, including cardiovascular mortality [162], and ICS have been shown to reduce markers of systemic inflammation, such as CRP [163]. However, a prospective study of high-dose ICS in COPD patients (TORCH study) showed a minimal reduction in all causes of mortality, indicating that it is unlikely that there is a significant clinical benefit of ICS on COPD comorbidities such as cardiovascular disease or lung cancer, which are the commonest causes of death [93].…”
Section: Inhaled Corticosteroidsmentioning
confidence: 99%